RISIKO PENGGUNAAN INPUT PADA USAHATANI PADI DI KABUPATEN KULON PROGO - Nanik Dara Senjawati; Sri Widodo; Slamet Hartono (Jurnal Dinamika Sosial Ekonomi, 2005)
The study is conducted in Keeamatan Giri Mulyo, Kecamatan Nanggulan, and Kecamatan Kalibawang by purposively. The primary data are collected from 117 sample respondents using cluster sampling. The analysis using Heteroscedastic Non Limer Least Square method by Multiplicative Heteroscedasticity Model. The result show that rice production was positively influenced by labor inputs, urea,TSP, and KCI. Meanwhile, rainfed low land, medium and low risk region have a negative effect to production. On the other hand, labor inputs, seeds, dry season, to make a negative contribution to variance of production. While, more of urea fertilizer increase the risk.Keywords: inputs risk, rice farming